Effect of Country of Origin on Brand Perception of Indian Consumer: A Study on Selected Electronics Products - Bathla, Aditi (Journal of Commerce and Trade, 2013)
In recent years, all the international and global companies from all over the world with any origin try to capture market share in other countries. Marketers have to consider the impact of country of origin in society to which they try to apply their marketing strategies to get the market share because each country have its own people and its own culture, as result they have their own purchasing behaviour and purchasing decision making in facing the foreign and domestic products. In this research paper, it has been tried to examine generally the impact of country of origin on consumers purchasing behaviour in electronics (Devices) industry. People have become quality and price conscious and prefer to buy products though imported which have better quality and pricing than the products available in the domestic market. Als0 this paper helps to understand how multinationals can use this information to design their strategies to place their products in foreign market.